Principles of gestalt psychology - Koffka, Kurt, 1886-1941. ([y.y.])
xi, 720 s.
Keywords: "In this book, Kurt Koffka reformulates the basic question of perception. In the past it had often been assumed that there was really no need to explain the features of veridical perception. Here Koffka rejects this approach: regardless of the veridicality of perception, the researcher must always ask the question, "Why do things look as they do?" The book details the phenomenological and holistic approach to this question which the Gestalt movement embraced, while also reviewing the extensive research which had been conducted up to that time in support of the Gestalt orientation." --